2004
DOI: 10.1051/0004-6361:20034539
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances of planetary nebulae towards the Galactic anticenter

Abstract: Abstract. In this paper we report new observations and derive chemical abundances for a sample of 26 planetary nebulae (PN) located in the anticenter direction. Most of these nebulae are far away objects, located at Galactocentric distances greater than about 8 kpc, so that they are particularly useful for the determination of the radial gradients at large distances from the galactic center. A comparison of the present results with previously determined abundances suggests that the radial abundance gradients f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 36 publications
5
46
0
Order By: Relevance
“…These metallic abundances agree with the expected [Fe/H] at such a distance, i.e., [Fe/H] ≈ −0.4 dex to [Fe/H] ≈ −0.6 dex and this puts these two clusters on the plateau already devised through analysis of other objects such as isolated hot stars (Cayrel de Strobel et al 1997;Daflon & Cunha 2004), planetary nebula (Costa et al 2004), Cepheids (Fry & Carney 1997), etc., though more limited in distance. We cannot argue against or in favour of the existence of a radial metallicity gradient (see Chen et al 2003;Koen & Lombard 2007).…”
Section: The Clusters and Spiral Structuresupporting
confidence: 84%
“…These metallic abundances agree with the expected [Fe/H] at such a distance, i.e., [Fe/H] ≈ −0.4 dex to [Fe/H] ≈ −0.6 dex and this puts these two clusters on the plateau already devised through analysis of other objects such as isolated hot stars (Cayrel de Strobel et al 1997;Daflon & Cunha 2004), planetary nebula (Costa et al 2004), Cepheids (Fry & Carney 1997), etc., though more limited in distance. We cannot argue against or in favour of the existence of a radial metallicity gradient (see Chen et al 2003;Koen & Lombard 2007).…”
Section: The Clusters and Spiral Structuresupporting
confidence: 84%
“…Frinchaboy et al (2013) measured a single radial fit of −0.09 dex kpc −1 for their sample of open clusters observed with APOGEE, but find that it is potentially better fit with two components: a steeper gradient of −0.2 dex kpc −1 between 7.9 < R < 10 kpc, and a flat radial gradient for clusters with R > 10 kpc. Several previous studies (Costa et al 2004;Jacobson et al 2011b;Yong et al 2012) have shown evidence for a transition to a flat radial gradient at large Galactocentric radii in the plane, with the transition occurring between 10 and 14 kpc. This flattening of the radial gradient is not observed with Cepheids Luck & Lambert 2011;Lemasle et al 2013).…”
Section: Intermediate Radiimentioning
confidence: 85%
“…Some authors have suggested a bimodal distribution of the oxygen abundances (Costa et al 2004;Magrini et al 2009;Yong et al 2012;Korotin et al 2014 and references therein) with a flattening starting at around 9-13 kpc from the Galactic centre. Korotin et al (2014), for example, suggest a double linear distribution with a slope of −0.056 dex kpc −1 until about R gc = 12 kpc and a flatter one of −0.033 dex kpc −1 at more dis- …”
Section: Oxygenmentioning
confidence: 99%